1995
DOI: 10.1159/000109797
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Morbidity due to Head Injuries in New Zealand in 1980–1988

Abstract: We studied the morbidity in New Zealand using hospital discharge data from 1980 to 1988, and found a reduced head injury (HI) rate over this time overall, but no change in the rate among Maori males and an increased rate among Maori females. In 1988 the rate was 228/100,000 with peaks among males and females aged under 10, males aged 15–25, and both sexes over 84 years old. The rate among young Maori males was higher than in other groups until the age of 55. Motor vehicle crashes caused most head injuries, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…New Zealand's 2006 practice guidelines for TBI [22] note significant ethnic disparities in TBI incidence. In contrasting the 1980-1988 data reported by Caradoc-Davis and Dixon [2] to the present data, it can be observed that while the incidence of the entire population (1997/1998) does not appear to have changed, the overall incidence for Maori males (1997/1998 and 1998/1999) is much lower than that previously published, with a similar reduction for Maori females. This suggests that while disparities do still exist, this gap is narrowing.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…New Zealand's 2006 practice guidelines for TBI [22] note significant ethnic disparities in TBI incidence. In contrasting the 1980-1988 data reported by Caradoc-Davis and Dixon [2] to the present data, it can be observed that while the incidence of the entire population (1997/1998) does not appear to have changed, the overall incidence for Maori males (1997/1998 and 1998/1999) is much lower than that previously published, with a similar reduction for Maori females. This suggests that while disparities do still exist, this gap is narrowing.…”
Section: Discussioncontrasting
confidence: 96%
“…The results of this study suggest that the overall ageadjusted hospital-based incidence of traumatic head injury in New Zealand in 2003/2004 (342/100,000/year for total and 458/100,000/year for Maori people) is notice- ably greater (especially in Maori people) when compared to the estimated 200-300 people per 100,000 annually elsewhere [1] as well as the overall age-adjusted New Zealand rate of 228 per 100,000 reported by Caradoc-Davies and Dixon [2] in 1980-1988. While it is informative to note this increase relative to international studies which have used similar hospitalization databases, the accuracy of these hospital-based data remains questionable as they are still likely to exclude cases of mild brain injury (estimated 70-90% of all TBI cases), many of whom do not seek medical care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations